Kajian Nilai-Nilai Kearifan Lokal Dalam Garapan Tari Kreasi “Babuai Kain” - Putri Novrialni; Indrayuda Indrayuda (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to find out the value of Local Wisdom in the work of the Babuai Kain Dance at Sanggar Sikambang Group. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments and assisted by stationery and mobile phone supporting instruments. The data of this study uses primary data and secondary data. Data was collected through literature studies, observations, interviews, documentation. The steps to analyze data are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the value of local wisdom in the performance and work of the Babuai Kain Dance in Kenagarian Kambang Barat consists of moral values, mutual cooperation values, social values, ethical values, religious values, aesthetic values and beauty. The moral value in the Babuai Kain dance can distinguish between good and bad in individual relationships and to the community who will meononon the dance performance. The value of Gotong is the result of the Babuai Kain dance being deliberated together. The social value is that during the dance performance, the enthusiasm of the community in watching this Babuai Kain dance. The ethical value is that before carrying out an activity, be it a rehearsal or a performance of the Babuai Kain dance, first ask permission from the ninik mamak and other village leaders. The value of religion is in its appearance starting after the dhuhur prayer or after rest, prayer, eating (Ishoma). The aesthetic value and beauty are seen in the dance movements, costumes, props and dance accompaniment.